Red and white Chinook salmon: genetic divergence and mate choice. Issue 6 (1st March 2016) - Lehnert, Sarah J.; Pitcher, Trevor E.; Devlin, Robert H.; Heath, Daniel D.
Abstract: Chinook salmon ( Oncorhynchus tshawytscha ) exhibit extreme differences in coloration of skin, eggs and flesh due to genetic polymorphisms affecting carotenoid deposition, where colour can range from white to bright red. A sympatric population of red and white Chinook salmon occurs in the Quesnel River, British Columbia, where frequencies of each phenotype are relatively equal. In our study, we examined evolutionary mechanisms responsible for the maintenance of the morphs, where we first tested whether morphs were reproductively isolated using microsatellite genotyping, and second, using breeding trials in seminatural spawning channels, we tested whether colour assortative mate choice could be operating to maintain the polymorphism in nature. Next, given extreme difference in carotenoid assimilation and the importance of carotenoids to immune function, we examined mate choice and selection between colour morphs at immune genes (major histocompatibility complex genes: MHC I‐A1 and MHC II‐B1). In our study, red and white individuals were found to interbreed, and under seminatural conditions, some degree of colour assortative mate choice (71% of matings) was observed. We found significant genetic differences at both MHC genes between morphs, but no evidence of MHC II‐B1‐based mate choice. White individuals were more heterozygous at MHC II‐B1 compared with red individuals, and morphs showed significant allele frequency differences at MHC I‐A1. Although colour assortative mate choice is likely not a primary mechanism maintaining the polymorphisms in the population, our results suggest that selection is operating differentially at immune genes in red and white Chinook salmon, possibly due to differences in carotenoid utilization.